Association of Body Mass Index With Tuberculosis Mortality: A Population-Based Follow-Up Study. Issue 1 (January 2016) - Yen, Yung-Feng; Chuang, Pei-Hung; Yen, Muh-Yong; Lin, Shu-Yi; Chuang, Peing; Yuan, Mei-Jen; Ho, Bo-Lung; Chou, Pesus; Deng, Chung-Yeh
Abstract : Abstract: Evidence regarding the association between body mass index (BMI) and mortality in TB patients is limited and inconsistent. We investigated the effect of BMI on TB-specific and non-TB-specific mortality in TB patients. All adult Taiwanese with TB in Taipei, Taiwan, during 2011 to 2012 were included in this retrospective cohort study. Multinomial logistic regression was used to evaluate associations of BMI with cause of death in TB patients. Of the 1608 eligible patients, 83.6% (1345) were successfully treated, 3.3% (53) died of TB-specific causes, and 13.1% (210) died of non-TB-specific causes. Mean age was 64.6 years, and 67.5% of patients were male. After controlling for potential confounders, underweight was significantly associated with higher risks of all-cause mortality (adjusted odds ratio [AOR], 1.66; 95% confidence interval [CI], 1.21–2.30), TB-specific mortality (AOR, 2.14; 95% CI, 1.18–3.89), and non-TB-specific mortality (AOR, 1.58; 95% CI, 1.11–2.25) during TB treatment, while overweight was not. When gender differences on the association of BMI with mortality were considered, underweight only significantly increased risks of TB-specific (AOR, 2.37; 95% CI, 1.19–4.72) and non-TB-specific mortality (AOR, 1.58; 95% CI, 1.05–2.37) during treatment in male patients, but not female subjects. The present findings indicate that underweight was associated with higher risks of TB-specific and non-TB-specific mortality during TB treatment, particularly in male patients. Abstract : Supplemental Digital Content is available in the text